Maxillary mesiodens in late medieval age archaeological skeletal remains from Rudina, Croatia - Banjšak Luka; Viroubal Vlasta; Katanec Tomislav; Miličević Ante (Medicinski fakultet i Klinika za stomatologiju, Niš, 2022)
Introduction: The occurrence of mesiodens is somewhat rare, but amongpatients with any kind of supernumerary teeth, it is rather common. From an anthropological point of view, it is interesting to confirm the development of mesiodens in various historical ages. Case report analyses a mesiodens and the surrounding skeletal remains dating from the late medieval ages (13th -16th centuries) which confirms the incidence of the mesiodens and presents the conclusion that historically, mesiodens, as a form of supernumerary teeth has been present throughout history. Conclusion finding of a mesiodens in an archaeological context proves that the occurrence of this type of accessory teeth has been present for at least half a millennium.